The relationship of genotype to cognitive outcome in galactosaemia. Issue 3 (1st September 2000) - Shield, J P H; Wadsworth, E J K; MacDonald, A; Stephenson, A; Tyfield, L; Holton, J B; Marlow, N
Abstract : AIMS: To evaluate the cognitive outcome of a cohort of children with galactosaemia in relation to genotype. METHODS: The cohort was drawn from children notified to the British Paediatric Surveillance Unit galactosaemia study which ran from 1988 to 1990. Cognitive outcome was assessed using the Wechsler Intelligence Scale for Children or the Wechsler Preschool and Primary Scale of Intelligence. Parents completed a questionnaire detailing educational status, and the attending paediatrician returned a questionnaire regarding age at diagnosis and biochemical outcome over the previous two years. RESULTS: A total of 45 children were genotyped: 30 were homoallelic for the Q188R mutation, the remainder being heteroallelic for Q188R with K285N (n = 4), L195P (n = 4), or other mutations (n = 7). Psychometric evaluation was available in 34 cases: mean full scale IQ was 79, verbal quotient 79, and performance quotient 82. Genotype was not related to galactose-1-phosphate (Gal-1-P) concentrations. However, children homoallelic for the Q188R mutation had significantly lower IQ scores than those who were heteroallelic (73.6 v 94.8). This difference was independent of social and demographic influences and Gal-1-P concentrations over the previous two years. CONCLUSIONS: In children with galactosaemia, cognitive outcome appears to relate to genotype rather than metabolic control, as reflected by Gal-1-P concentrations. The value of measuring Gal-1-P concentrations routinely once successfully established on a galactosaemia diet is questionable as concentrations do not appear to affect outcome. In the UK population, homozygosity for the Q188R mutation is invariably associated with a poor outcome, and there is evidence that variability in neurocognitive outcome is at least part dependent on allelic heterogeneity.